Теоретичні основи формування етнокультурної компетентності майбутнього вчителя-філолога - Гончарук, Валентина (My University, 2018)
Сьогодні молодій людині необхідно оволодіти здатністю аналізувати й оцінювати досягнення національної культури, орієнтуватися в етнокультурному просторі нації. Таке молоде покоління українців зможе підготувати вчитель-філолог, у якого на високому рівні буде сформовано етнокультурну компетентність. Мета дослідження: визначити й обґрунтувати теоретичні основи формування етнокультурної компетентності вчителя-філолога у закладах вищої освіти. Серед ключових компетентностей випускника загальноосвітньої школи виділено загальнокультурну компетентність, у структурі якої головне місце належить етнокультурній. У культурологічній компетентності вчителя-філолога виокремлено таку складову, як етнокультурна компетентність, що буде вказувати на його здатність усвідомлювати себе як носія певної етнокультури. З’ясовано, що така компетентність особистості охоплює знання чималої кількості елементів етнічної культури, починаючи з елементарних невербальних комунікацій (жести, ритми, пози, міміка, вираз очей) до узагальнюючих моральних і правових норм, звичаїв. Встановлено, що етнокультурно компетентна особистість свідомо взаємодіє з культурно багатозначущими предметами, створює складний соціально-культурний простір. Зроблено висновок, що процес формування етнокультурної компетентності не завершується із закінченням школи, а відбувається упродовж усього життя людини, однак певний ступінь її сформованості у шкільні роки стане визначальним на шляху становлення особистості. Тому заклад вищої освіти має спрямовувати свою навчально-виховну роботу на формування етнокультурної компетентності майбутнього вчителя-філолога, від якого буде залежати рівень сформованості її в учнів, а від них – і наступних поколінь українців.A young man needs to learn the ability to analyze and evaluate the national culture achievements, to know the ethno-cultural space of the nation. Young generation of Ukrainians will be able to prepare a philologist who will have a high level of ethnocultural competence. In the new educational documents the cultural competence is among the key competences of the teacher-philologist. This competence implies teacher's knowledge of the vocabulary with the national-cultural component, the names of objects and phenomena of traditional Ukrainian life, customs, traditions, folk art. Among the key competences of a secondary school graduate we take into account the general cultural competence, the structure of which is dominated by ethno-cultural one. The ethnocultural competence of the person includes knowledge of a considerable number of elements of ethnic culture, ranging from elementary non-verbal communication (gestures, rhythms, poses, facial expressions, glances) to generalizing moral and legal norms, customs. In the above-mentioned cultural competence of a teacher-philologist, we also single out such component such the ethnocultural competence, which will indicate its ability to perceive itself as a carrier of a particular ethnoculture. Ethnoculture concentrates a diverse spectrum of ethnic attributes manifestation, integrates, preserves, reproduces and, in a certain way, transforms the gains of various spheres of activity of particular nation. An ethno-cultural person consciously interacts with culturally significant objects and creates a complex socio-cultural space. The process of ethnocultural competence formation does not end with the school graduation, but happens throughout the life of a person. However, a certain degree of its formation during school years plays an important role in the personality formation. Therefore, higher education institution should direct its educational work on the formation of the ethnocultural competence of the future teacher-philologist, which will depend on the level of formation of such competence of the students, and later of the next generations of Ukrainians. This work provides for the future philologists obtaining the objective knowledge of Ukrainian ethnic culture, spiritual and moral values and mental features of the Ukrainian nation.
Keywords: культурологічна компетентність; загальнокультурна компетентність; етнокультурна компетентність; етнокультура; процес формування етнокультурної компетентності; майбутні вчителі-філологи